Progress of new-onset diabetes after liver and kidney transplantation - Zhang, Zhen; Sun, Jianyun; Guo, Meng; Yuan, Xuemin (Frontiers in Endocrinology, 2023)
Organ transplantation is currently the most effective treatment for end-stage organ failure. Post transplantation diabetes mellitus (PTDM) is a severe complication after organ transplantation that seriously affects the short-term and long-term survival of recipients. However, PTDM is often overlooked or poorly managed in its early stage. This article provides an overview of the incidence, and pathogenesis of and risk factors for PTDM, aiming to gain a deeper understanding of PTDM and improve the quality of life of recipients.